Multiple dimensions of embodiment in medical practices - Slatman, Jenny (Medicine, health care, and philosophy, 2014)
In this paper I explore the various meanings of embodiment from a patient’s perspective. Resorting to phenomenology of health and medicine, I take the idea of ‘lived experience’ as starting point. On the basis of an analysis of phenomenology’s call for bracketing the natural attitude and its reduction to the transcendental, I will explain, however, that in medical phenomenological literature ‘lived experience’ is commonly one-sidedly interpreted. In my paper, I clarify in what way the idea of ‘lived experience’ should be revisited and, subsequently, what this reconsideration means for phenomenological research on embodiment in health and medicine. The insight that the body is a condition of possibility for world-disclosing yet, at the same time, itself conditioned by this world forces us to not only zoom in on the body’s subject-side, but also on its object-side. I argue that in order to render account for this double body ontology, phenomenology should include empirical sociological analyses as well. I thus argue in favor of the idea of a socio-phenomenology. Drawing on material from my own research project on embodied self-experiences after breast surgery, I show how this approach can be fruitful in interpreting the impact of disfigurements on a person’s embodied agency, or a person’s ‘I can’.